MANAJEMEN STRATEGI PENGEMBANGAN HALAL TOURISM DI JOMBANG (STUDI PADA MAKAM KH. ABDUL WAHAB HASBULLAH) - Laila Ainul Jannah; Ahmad Nur Ismail; Khotim Fadhli; Arivatu Ni’mati Rahmatika (STIE Bakti Bangsa Pamekasan, 2021)
Abdul Wahab Hasbullah is one of the tourism potentials possessed by Jombang Regency, many of the advantages possessed by the KH. Abdul Wahab Hasbullah which can be developed to become a religious pilgrimage tour. The process of developing tourism in KH. Abdul Wahab Hasbullah is expected to have many positive impacts both from a social and economic perspective in the life of the surrounding community. This study uses a qualitative method with a phenomenological approach. The research subject is KH. Abdul Wahab Hasbullah. The object of his research is the concept of developing the religious tourism area of ??the Tomb of KH. Abdul Wahab Hasbullah using Halal Tourism Strategy Management. In collecting data, the researcher digs up some information from various media sources or websites and goes directly to the field, describes and constructs the existing reality and then draws conclusions. The purpose of this study is to formulate directions for the development of the religious tourism area of ??the Tomb of KH. Abdul Wahab Hasbullah. The impact of the development of religious tourism in the Tomb of KH. Abdul Wahab Hasbullah, namely in the aspects of tourism marketing, infrastructure, tourist facilities, increasing human resources (HR), and community culture.